A Morphometric study of the mandibular foramen in dry adult human mandibles. - Dr Anjana Baitalik, Dr Amitabha Das, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Located on the medial side of the mandibular ramus, the mandibular foramen (MF)is a noticeable and vital anatomical structure. This incision is where the inferior alveolar nerve and veins emerge. Blood reaches the jaw, lower teeth, and surrounding tissues via these veins and nerves. Aim: The current study aimed to offer crucial baseline data for the anatomical literature and clinical practice by conducting a thorough morphometric analysis of the mandibular foramen in dry adult human mandibles. This was done to offer necessary information